2014
DOI: 10.1210/jc.2013-4084
|View full text |Cite
|
Sign up to set email alerts
|

Central Precocious Puberty in a Girl and Early Puberty in Her Brother Caused by a Novel Mutation in the MKRN3 Gene

Abstract: We report a novel MKRN3 mutation (p.C340G) in a girl with CPP and her brother with early puberty. MKRN3 alterations should be suspected in all cases with familial CPP or early puberty, especially if male patients are also involved or the precocious puberty trend does not follow the usually observed mother-to-daughter inheritance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 18 publications
6
86
0
2
Order By: Relevance
“…These mutations were found in 15 patients from five families. Thirteen other patients with iCPP and MKRN3 mutations, from six families, have since been described (12,13,14,15). In our study, heterozygous MKRN3 mutations were found in 14 of 46 index patients with iCPP (30%).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…These mutations were found in 15 patients from five families. Thirteen other patients with iCPP and MKRN3 mutations, from six families, have since been described (12,13,14,15). In our study, heterozygous MKRN3 mutations were found in 14 of 46 index patients with iCPP (30%).…”
Section: Discussionsupporting
confidence: 55%
“…This may reflect a recruitment bias and the well-known higher prevalence of precocious puberty in girls than in boys. No accurate information about age at puberty onset was available for three previously reported cases of iCPP in male patients with MKRN3 mutations (11,12,13). The other five boys had a median age at Tanner stage 2 of 8.25 years (8-8.5), suggesting that the decrease in age at puberty onset was smaller for boys than for girls.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although ICPP is typically inherited from mother to daughter and affects mostly girls (12), mutations in MKRN3 seem to be equally distributed among males and females, although the effect on females seems to be somewhat stronger (3,6). In our family, the girl's age at the onset of puberty was comparable to previous reports in female MKRN3 mutation carriers (range: 3.0-6.5 y; mean 5.9; median 6.0 y) (13).…”
Section: Discussionmentioning
confidence: 98%
“…The p.Arg345His mutation identified in this study is situated in the C3HC4 RING domain of MKRN3 responsible for ubiquitin ligase activity of the protein. Two of the four previously reported missense mutations in ICPP patients (p.Arg365Ser and p.Cys340Gly) are situated in this same domain (3,6), but the functional consequences of these mutations, although predicted to be deleterious and disrupt the tertiary protein structure (6), have not been confirmed. The two other reported missense mutations, p.Phe417Ile and p.His420Gln, are located in the third RNA-binding C3H zinc-finger domain and are also predicted to have deleterious effects (7,9).…”
Section: Discussionmentioning
confidence: 99%